1996
DOI: 10.1093/nar/24.21.4158
|View full text |Cite
|
Sign up to set email alerts
|

Proximal promoter elements of the human zeta-globin gene confer embryonic-specific expression on a linked reporter gene in transgenic mice

Abstract: We have investigated the transcriptional regulation of the human embryonic zeta-globin gene promoter. First, we examined the effect that deletion of sequences 5' to zeta-globin's CCAAT box have on zeta-promoter activity in erythroid cell lines. Deletions of sequences between -116 and -556 (cap = 0) had little effect while further deletion to -84 reduced zeta-promoter activity by only 2-3-fold in both transiently and stably transfected erythroid cells. Constructs containing 67, 84 and 556 bp of zeta-globin 5' f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We considered the possibility that this pattern of expression might represent an artifact of the ␤-galactosidase reporter gene, since it has been reported that the ␤-galactosidase cassette interferes with the ability of the ␤-globin locus control region to confer position-independent expression (30), and it has been suggested that the ␤-galactosidase sequence may act as a nucleation point for the formation of heterochromatin in definitive erythroid cells (71). However, several groups have shown that a variety of erythroid enhancers, including the ␤-globin locus control region (30,31), the ␣-globin Ϫ40 element (56,70), and the EKLF Ϫ950 promoter (77), can direct expression of ␤-galactosidase to definitive erythroid cells in transgenic mice. Instead, we favor the alternative explanation that the 3.7-kb fragment containing the ϩ40 region exhibits intrinsic specificity for the primitive erythroid lineage.…”
Section: Discussionmentioning
confidence: 99%
“…We considered the possibility that this pattern of expression might represent an artifact of the ␤-galactosidase reporter gene, since it has been reported that the ␤-galactosidase cassette interferes with the ability of the ␤-globin locus control region to confer position-independent expression (30), and it has been suggested that the ␤-galactosidase sequence may act as a nucleation point for the formation of heterochromatin in definitive erythroid cells (71). However, several groups have shown that a variety of erythroid enhancers, including the ␤-globin locus control region (30,31), the ␣-globin Ϫ40 element (56,70), and the EKLF Ϫ950 promoter (77), can direct expression of ␤-galactosidase to definitive erythroid cells in transgenic mice. Instead, we favor the alternative explanation that the 3.7-kb fragment containing the ϩ40 region exhibits intrinsic specificity for the primitive erythroid lineage.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of basal transgene expression observed in Tg.AC mice re¯ected the tissue-and development-speci®c expressions of the z-globin gene. Only 67 bp of sequence proximate to the transcription start site was reported to be required to confer the erythroid-speci®c expression of the z-globin gene [13,14]. No apparent previously recognized enhancer sequence was contained within the 78-bp deletion of the z-globin promoter sequence in N 2 nonresponder mice.…”
Section: DI Is Sc Cu Us Ss Si Io On Nmentioning
confidence: 99%
“…1993). Another study showed that the embryonic specific activation of the ζglobin gene is conferred by the 67 bp ζ -promoter fragment containing only a CACCC and TATA box (Pondel et al . 1996).…”
Section: Introductionmentioning
confidence: 99%